Measurement of high temperature full-field strain up to 2000 °C using digital image correlation. (25th January 2017) - Wang, Wei; Xu, Chenghai; Jin, Hua; Meng, Songhe; Zhang, Yumin; Xie, Weihua
Abstract: Understanding the deformation and strain at elevated temperature is a critical factor for the stability of aerodynamic shape, and an important consideration for the thermal protection system design. However, accurate measurement of deformation and strain at high temperatures is a challenge. Here, we present a measurement study for full-field strain mapping up to 2000 °C using digital image correlation (DIC) method, which mainly depends on the quality of speckle patterns on the specimen surface. In our study, the strain values are analyzed by DIC method while specimens are heated using a large electric current. Improvements in filtering and speckling allow the measured temperatures using this method to reach 2000 °C. We confirmed the validity of this method by comparison of measured Young's modulus values with reference data for Inconel 718 Ni-based superalloy and graphite at different temperatures. Additionally, the full-field strain and Young's modulus were demonstrated for a carbon fiber-reinforced carbon (C/C) composite uniaxial tensile specimen at 2000 °C.